Power foods cookbook : 200 simple & satisfying recipes - Mills, Jackie, 1961-; Weight Watchers International (2011)
Presents recipes that use one or more Weight Watchers power foods and that fit in the Weight Watchers PointsPlus program
Includes index
"ICP# 11187"--Page 4 of cover
Keywords: Reducing diets -- Recipes; Low-calorie diet -- Recipes; Cookbooks; Recipes; Cookbooks